(untitled) (Ornitología Colombiana, 2021)
The Ash-breasted Tit-Tyrant (Anairetes alpinus) is a range-restricted flycatcher (Tyrannidae) inhabiting the high Andes of Peru, Bolivia, and Argentina. I provide the first description of nest architecture for this species based on a nest encountered in southern Peru. The nest was a deep, compact cup of moss, thickly but loosely lined with feathers and built 1.4 m above the ground in a hanging epiphyte clump. It was similar in architecture and means of support to the nests of other Anairetes, all of which also share an internal lining of feathers.